Resting‐State Functional Connectivity Predicts STN DBS Clinical Response. Issue 3 (19th November 2020) - Younce, John R.; Campbell, Meghan C.; Hershey, Tamara; Tanenbaum, Aaron B.; Milchenko, Mikhail; Ushe, Mwiza; Karimi, Morvarid; Tabbal, Samer D.; Kim, Albert E.; Snyder, Abraham Z.; Perlmutter, Joel S.; Norris, Scott A.
ABSTRACT: Background: Deep brain stimulation of the subthalamic nucleus is a widely used adjunctive therapy for motor symptoms of Parkinson's disease, but with variable motor response. Predicting motor response remains difficult, and novel approaches may improve surgical outcomes as well as the understanding of pathophysiological mechanisms. The objective of this study was to determine whether preoperative resting‐state functional connectivity MRI predicts motor response from deep brain stimulation of the subthalamic nucleus. Methods: We collected preoperative resting‐state functional MRI from 70 participants undergoing subthalamic nucleus deep brain stimulation. For this cohort, we analyzed the strength of STN functional connectivity with seeds determined by stimulation‐induced (ON/OFF) 15 O H2 O PET regional cerebral blood flow differences in a partially overlapping group (n = 42). We correlated STN‐seed functional connectivity strength with postoperative motor outcomes and applied linear regression to predict motor outcomes. Results: Preoperative functional connectivity between the left subthalamic nucleus and the ipsilateral internal globus pallidus correlated with postsurgical motor outcomes ( r = −0.39, P = 0.0007), with stronger preoperative functional connectivity relating to greater improvement. Left pallidal‐subthalamic nucleus connectivity also predicted motor response to DBS after controlling for covariates. Discussion: Preoperative pallidal‐subthalamic nucleus resting‐state functional connectivity predicts motor benefit from deep brain stimulation, although this should be validated prospectively before clinical application. These observations suggest that integrity of pallidal‐subthalamic nucleus circuits may be critical to motor benefits from deep brain stimulation. © 2020 International Parkinson and Movement Disorder Society